Monitoring and Analysis of Pore and Earth Pressure at the Pile Surface Using Piezoresistive Silicon Pressure Transducers - Wang, Yonghong; Huang, Yongfeng; Zhang, Mingyi; Ma, Jiaxiao (Frontiers in Materials, 2021)
The piezoresistive silicon pressure transducers based on the piezoresistive effect have demonstrated their potential in the accurate monitoring of pressure. However, their usage in the pore and earth pressure monitoring at the pile surface under hydraulic jacking has not yet been explored. In this study, two self-made model piles (one is a closed-ended pile and the other is an open-ended pile) were instrumented with piezoresistive silicon earth transducers and pore pressure transducers and then driven into the soil using a hydraulic jack. A comprehensive investigation was first carried out for the structure of the model piles, the installation procedure of the transducers, and the composition of the test system. The pore and earth pressure measurements of the transducers were used for the evaluation of the distribution of the pore pressure, excess pore pressure, radial earth pressure, and radial effective earth pressure. The model test results indicate that the piezoresistive silicon pressure transducers are suitable for monitoring the pore and earth pressure at the pile surface during jacking. In addition, the pore pressure, excess pore pressure, radial earth pressure, and effective radial earth pressure along the test piles were affected by the penetration depth and the pile end form.